"Grab Your Culture and Walk with the Global": Ladakhi Students' Negotiation of Cultural Identity in the Context of Globalization-Based Acculturation. (April 2017) - Ozer, Simon; Bertelsen, Preben; Singla, Rashmi; Schwartz, Seth J.
The globalization-based acculturation process in the Indian Himalayan region of Ladakh represents a highly complex network of intercultural interactions. Ladakhi youth negotiate their cultural orientation and identity in relation both (a) to indirect intercultural exposure through media and (b) to intermittent cultural contact through tourism in Ladakh. Additionally, many Ladakhi students take sojourns in large Indian cities. Like other Eastern populations exposed to cultural globalization, young Ladakhis are influenced by several local and global cultural streams. Within this acculturative process, Ladakhi youth are caught between ambiguous societal pressures toward both tradition and change. Through in-depth interviews, in the present study we investigated the negotiations of eight Ladakhi students' cultural identity in Leh (Ladakh) and Delhi. In doing so, we drew pragmatically on theories of multiculturalism and dialogical self. Participants reported negotiating their cultural identity through dialogue between various personal, cultural, religious, and social voices, where these voices require selectively incorporating various cultural elements within the parameters established by societal constraints. Results indicate the vast complexity and dynamics within the Ladakhi acculturation process, with multiple interacting cultural streams, religions, and significant sociohistorical factors calling for an in-depth qualitative approach to elucidate the processes underlying globalization-based acculturation.